1996
DOI: 10.1016/s0092-8674(00)81364-1
|View full text |Cite
|
Sign up to set email alerts
|

Regions in β-Chemokine Receptors CCR5 and CCR2b That Determine HIV-1 Cofactor Specificity

Abstract: Macrophage-tropic (M-tropic) HIV-1 strains use the beta-chemokine receptor CCR5, but not CCR2b, as a cofactor for membrane fusion and infection, while the dual-tropic strain 89.6 uses both. CCR5/2b chimeras and mutants were used to map regions of CCR5 important for cofactor function and specificity. M-tropic strains required either the amino-terminal domain or the first extracellular loop of CCR5. A CCR2b chimera containing the first 20 N-terminal residues of CCR5 supported M-tropic envelope protein fusion. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
308
3
8

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(342 citation statements)
references
References 40 publications
23
308
3
8
Order By: Relevance
“…In addition, we used a singlestep entry assay that has a definite linear range and that may be more accurate than a syncytium forming assay for quantifying the ability of different receptors to support HIV-1 envelope-mediated membrane fusion. Other data in Rucker et al (42) indicate that HIV-1 envelope glycoprotein-induced syncytium formation is sensitive to modifications of the CCR5 N terminus. This conclusion is supported in this study with a receptor whose expression and structural integrity are verified.…”
Section: Chemokine Signaling and Hiv-1 Entry On Ccr5 6856 Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, we used a singlestep entry assay that has a definite linear range and that may be more accurate than a syncytium forming assay for quantifying the ability of different receptors to support HIV-1 envelope-mediated membrane fusion. Other data in Rucker et al (42) indicate that HIV-1 envelope glycoprotein-induced syncytium formation is sensitive to modifications of the CCR5 N terminus. This conclusion is supported in this study with a receptor whose expression and structural integrity are verified.…”
Section: Chemokine Signaling and Hiv-1 Entry On Ccr5 6856 Discussionmentioning
confidence: 90%
“…Rucker et al (42) have used constructs similar to 2M5 and observed HIV fusion activity comparable with that of wild-type CCR5. Several possibilities could account for this inconsistency with our data.…”
Section: Chemokine Signaling and Hiv-1 Entry On Ccr5 6856 Discussionmentioning
confidence: 99%
“…The aim was to identify CCR5 mutants that still supported HIV-1 entry, but that were less sensitive, or insensitive, to TAK-779 inhibition. We first evaluated wellcharacterized alanine-replacement mutants of the extracellular domain of CCR5 (30,31), because the gp120-binding site maps to this region, in particular, the Nt (30,31,(35)(36)(37)(38). However, alanine substitutions of residues in the extracellular domain had little or no effect on the antiviral activity of TAK-779; the mutant receptors still supported HIV-1 entry and were still sensitive to TAK-779 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, small molecule inhibitors of HIV-1 entry by means of CXCR4 block the binding of mAb 12G5 to ECL-2 of CXCR4 (21)(22)(23). A further complexity is that mutagenesis studies have implicated the CCR5 Nt as being critical for gp120 binding (30,31,(35)(36)(37)(38), yet alanine substitutions in the Nt have, paradoxically, no effect on the antiviral action of TAK-779. One interpretation of the ligand binding experiments is that there is more overlap between the binding sites for TAK-779 and gp120 than there is between the TAK-779 binding site and the mAb epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…The more distal regions of the V3 loop and bridging sheet are thought to interact with the ECLs of CCR5, with ECL2 representing a key determinant (10,12,20,28). Given the sequence variability inherent in the gp120 subunit, it is perhaps not surprising that there is some degree of plasticity in these interactions, as evidenced by the fact that mutations introduced into CCR5 can have markedly different effects on virus infection depending on the virus strain being examined (20,44). Thus, there is some variability in the relative importance of the CCR5 NЈ-terminal domain and ECL2 in supporting infection by different HIV-1 strains (41).…”
Section: Discussionmentioning
confidence: 99%